Vorarbeiten zu einer Königsliste Kaukasisch-Iberiens. 1. Anfänge der Pharnabaziden - Schottky, Martin (Anabasis. Studia Classica et Orientalia, 2012)
Medieval Georgian historiography connects the rise of an Iberian kingdom with Alexander the Great. On the other hand, Iberian rulers are mentioned in classical sources only since lateHellenistic times. This is a strong argument for the opinion of Meißner (2000) to date the emergence of Iberian kingship not before the epoch of Mithradates VI of Pontus. The genesis was nevertheless not due to Mithradates himself. It was his ally and son-in-law Tigranes II of Armenia, who was able to subjugate the Iberians soon after his own accession (95 BC). He installed a governor, who was (more or less tacitly) allowed to call himself “king“, like other vassals of the king of kings Tigranes. This ruler was perhaps called Pharnabazus, in Georgian Parnawas (transliterated also P ́arnawaz), what was the name of the legendary first Iberian king in the time after Alexander. With the decline of the Pontic-Armenian alliance, the first name of a king appears in classical sources: in 65 BC Pompey subdued a certain Artoces. In 36 BC we hear of Pharnabazus (II), who was very probably Artoces ́ son and a grandson of his name-sake, the founder of the dynasty. So, at the turning point from Hellenism to the Roman Empire, Pharnabazid rule was firmly established in Iberia.